Corporate Social Responsibility and Employee Outcomes: A Moderated Mediation Model of Organizational Identification and Moral Identity - Wang, Wei; Fu, Ying; Qiu, Huiqing; Moore, James H.; Wang, Zhongming (Frontiers in Psychology, 2017)
Corporate social responsibility (CSR) research is not new, but its importance to today’s socially conscious market environment is even more evident in recent years. This study moves beyond CSR as simply the socially responsible actions and policies of organizations and focuses on the complex psychology of CSR as it relates to individuals within the organization. Given CSR can positively affect both the individuals within the organization and the organization itself, better understanding and leveraging the mechanisms and conditions of CSR that facilitate desired employee outcomes is crucial for organizational performance. However, scholars lack consensus in determining a theoretical framework for understanding how and under what conditions CSR will make an impact on employees and ultimately organizational performance. This study adds clarity by exploring the effect of perceived CSR on a more comprehensive set of employees’ attitudinal and behavioral reactions (i.e. turnover intention, in-role job performance, and helping behavior) via the mediating mechanism of organizational identification and the moderating condition of moral identity. Hypotheses were derived using social identity theory. Results were based on data obtained from 340 Chinese manufacturing employee-supervisor dyads. This study found that employees’ perceived CSR had an indirect relationship via organizational identification with each of the variables: 1) turnover intention, 2) in-role job performance, and 3) helping behavior. Specifically, the negative relationship between perceived CSR and turnover intention was stronger when employees had higher moral identity and the positive relationship between perceived CSR and in-role job performance and helping behavior was amplified by moral identity. Our findings show how the mediating mechanism of organizational identity and the moderating condition of moral identity work together to improve organizational effectiveness. The findings reveal several ways in which organizations can strategically focus their CSR and human resource efforts, such as applying this model and focusing on moral identity as a key indicator when evaluating employees.